The Cowboys, the Poets, the Professor... – Antonomasia in Croatian Sports Discourse - Grgić, Ana, kroatistica (Array, 2013)
News style (or journalistic style) relies on the frequent use of tropes, especially metaphors and metonymies. Previous research concerning Croatian newspapers (Ivas, 2004 ; Runjić-Stoilova, 2012) showed that antonomasia is also a very frequent trope both in the headlines and in the body of journal articles. The aim of our research was to further explore types of antonomasia in the sports news sub-style. The corpus consisted of three groups of sports news: (1) sports news articles in daily newspapers ; (2) articles in specialized sports newspapers and magazines ; (3) the prime- time sports news in the daily news program of the three Croatian national networks (HRT, Nova TV and RTL). Three conclusions can be drawn from the analysis: (1) sports antonomasias mostly substitute names of athletes, sports clubs and national selections ; (2) metonymic-based antonomasias are most frequently used ; (3) journalists tend to use antonomasia more frequently in written articles than in television news.